Lived experiences of how the care relationship in primary healthcare contributes to recovery from stress-related disorders: a reflective lifeworld research study - Markus Sjösten; Cecilia Fagerström; Ulrica Hörberg; Hanna Tuvesson (International Journal of Qualitative Studies on Health & Well-Being)
Purpose The aim of the study was to describe how the care relationship in primary healthcare has contributed to the recovery of persons with stress-related disorders. Methods This study was based on the phenomenological approach, Reflective Lifeworld Research (RLR). Fifteen persons who had recovered from stress-related disorders and who had experience of being cared for in primary healthcare were included. Lifeworld interviews were conducted, and the data were analysed according to the RLR principles of openness, flexibility and bridling. Results The participants experienced that the care relationship in primary healthcare contributed to their recovery from stress-related disorder by enabling them to land and be embraced in a safe relationship. This opened up a space for rest and growth that included time, being listened to and a permitting space for existential reflection based on one’s life story. The results also showed that a sense of disharmony in the care encounter constitutes a threat to recovery and reinforces vulnerability. Conclusions Sensing security and hope is a crucial element in the care relationship in primary healthcare when recovering from stress-related disorders. This includes the importance of being treated with respect, being given space to tell one’s story, being listened to and being supported in an existential reflection of one’s life situation.